Socio-economic, Psychological and Situational Causes of Suicides of Farmers in Vidarbha Region of Maharashtra (Indian Journal of Extension Education, 2013)
The study was undertaken for identification of various causes of suicides of farmers in highly suicide prone six districts of Vidarbha region of Maharashtra with exploratory design of social research. Total 200 victim families were selected by proportionate method of random sampling. It covers 178 villages and 34 tahsils of six districts of Vidarbha. The study revealed that low education level, large to medium family size with nuclear type of families, small and marginal rainfed holding with no source to access the irrigation, low productivity due to monsoon vagaries, low annual income, indebtedness, low socio-economic status, inability to fulfill important family responsibilities due to poor economic condition, alcohol drinking habit, personal and family members health problems and disputes, were causes of suicides among farmers of Vidarbha. All these causes were interrelated and they feed into each other and aggravate each other. All these identified causes were not common in all victims, but overall it reflects the poor socio-economic condition of the deceased farmers of Vidarbha. For improving this situation, policy makers have to think critically and take appropriate measures for improving economic condition of the farmers of Vidarbha.